Auditory discrimination in dyslexia - differences between university and non-university educated individuals - Pitt, A; Anna Pitt (2009)
It is still unresolved whether individuals with dyslexia suffer non-verbal auditory processing deficits that may explain their phonological problems. Many studies have shown that dyslexic individuals are poor at discriminating pure tones, and this deficit has been attributed to impaired rapid auditory processing. In order to investigate the temporal properties of auditory processing in dyslexia, I have therefore studied the pure tone discrimination abilities of dyslexics, and then analysed the effects of varying interstimulus interval, the amount of frequency difference, and the effect of adding distractor tones during the interstimulus interval. In an investigation of dyslexic individuals’ ability to remember sequences of tones or digits (tonal and digit recognition memory), Rose and Rosner (2005) found that their results were affected by the education their subjects had received. The university educated dyslexics showed little tone discrimination deficit, whereas the dyslexic participants who never attended university showed greater deficits. Therefore, another aim of this thesis was to further study these findings and to identify any auditory processing compensatory mechanisms used by dyslexics who have received higher education. In eight different auditory tasks, the majority of which I programmed, I found strong evidence of non-verbal auditory processing deficits in dyslexic individuals. The comparison of university and non-university groups showed that educational differences had clear effects on many of their abilities, and should not be underestimated. The results showed that: In general, dyslexics had poorer auditory frequency discrimination than controls. Dyslexics who did not attend university had lower performance on almost all the auditory tests than the university dyslexic or control groups. Unexpectedly, university educated dyslexics were less distracted by interrupting tones during frequency discrimination than university educated controls. In a tone sequence memory task, the university educated dyslexics compensated in their performance to a level not much below that of the university educated controls, and above the controls who did not go to university. The frequency recognition tasks positively correlated with literacy abilities, and were independent of general intelligence. The strongest correlations were in the non-university dyslexic group. The implications of these results are that not only do dyslexic individuals suffer from a low level, non-linguistic, auditory processing deficit, but those who do not get to university are less able to compensate for these difficulties. It is impossible to say if the higher performance in university educated dyslexics was due to compensation, or if their presence at university was due to a lack of these deficits in the first place. Nevertheless, since university educated dyslexics were better at resisting distractions this may underlie their ability to compensate. These findings could facilitate the creation of new teaching methods to support the development of dyslexics’ compensatory skills and new non-linguistic diagnostic aids. These would help with identifying dyslexia in second languages and enable earlier testing and identification, before reading failure exerts its inevitable negative effects on children’s self-confidence, happiness and future academic potential.